Mesh patch and anchors can improve clinical results of prosthetic replacement after resection of primary proximal humerus malignant tumor - Yang, Yongkun (Sci Rep, 2021)
The purpose of this study was to evaluate the functional results, complications and related factors of prosthesis reconstruction after malignant tumor resection of primary proximal humeral, and also evaluate whether soft tissue reconstruction with mesh patch and anchors can improve clinical results. From 2002 to 2016, forty-one patients were enrolled in this study. The pathological diagnosis contained 27 cases of osteosarcoma, 7 cases of chondrosarcoma and other primary malignant bone tumors. Both mesh patch and anchors were used in the reconstruction of joint capsule and the surrounding soft tissues in 27 cases. The mean postoperative follow-up was 60.6 months. The average active abduction angle and passive abduction angle was 33.5 (5–71) degrees and 72.4 (52–104) degrees. The prosthetic humeral head displacement was over 2 cm in 5 cases (12.2%). The average MSTS score was 23.1. The overall 5-year survival rate of prosthesis was 88.2%. The length of osteotomy, whether preserving deltoid muscle, whether applying mesh patch and anchors had significant effects on the abduction angle of shoulder joint; the length of osteotomy, whether applying mesh patch and anchors had significant effects on the degree of upward displacement of prosthesis. The application of both mesh patch and anchors in prosthesis reconstruction achieved more stable result and better function of shoulder joint. To ensure the stability of shoulder joint and the firm wrapping of surrounding soft tissue are key factors affecting the postoperative function.